Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Race, racisme, discriminations: anthologie de textes fondamentaux - Bessone, Magali; Sabbagh, Daniel (Hermann, 2015)
« La race n'est-elle qu'une chimère - une fiction collective aux effets pernicieux - ou est-elle un concept nécessaire à l'analyse et à l'éradication éventuelle du racisme et de ses conséquences? Cette catégorie ambiguë relève-t-elle de la biologie ou bien renvoie-t-elle à une réalité de nature socio-politique? Le racisme est-il d'abord un attribut des individus ou des institutions - un état mental fait de croyances et d'affects ou un système social? Toute discrimination raciale est-elle inévitablement raciste? Est-elle immorale et injuste même dans les cas où elle ne serait pas entièrement irrationnelle? Enfin, la discrimination positive est-elle justifiable? Telles sont quelques-unes des questions abordées dans ce recueil, qui propose une introduction au champ d'investigation que la race, le racisme et les discriminations constituent pour la philosophie - ici envisagée dans son articulation avec les sciences sociales. Il réunit dix textes majeurs, presque tous inédits en français. »
Section: 372 pages ; 23 cm.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; antiracisme; approches et analyses; cours; discipline; discriminations; europe; occident; phi4336; philosophie; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences